Warisan Budaya Pantun dalam Manuskrip Surat Incung - Hafiful Hadi Sunliensyar (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2022)
Pantun is one of the ancient poetry that is the cultural heritage of the society in the archipelago. At first, the Pantun tradition is an oral tradition that functioned for various purposes. However, Pantuns are also transformed into written form after. The text entity of the Pantun is inserted in various Hikayat Melayu and in local literary manuscripts, such as the Ulu manuscript and the Incung Kerinci manuscript. This study aims to identify Pantuns in the Incung manuscripts that have been translated. The result of this research shows that 14 Incung manuscripts containing the texts of Pantun. Its texts are categorized as “pantun biasa” dan “talibun” with distinctive characteristics. Its specific character is the existence of an interjection or a sentence containing interjection between the “sampiran” and “isi”. The availability of pantuns is only found in the Incung manuscript containing the prose of lamentations. The function of pantuns is as a